Factors that Affect Employee Loyalty in the Business Entity: Theoretical Insights - Vilkaitė-Vaitonė, Neringa; Sologubas, Simas (Jaunųjų mokslininkų darbai, 2019)
Employees are the main asset of a modern business entity, they have an impact on its performance. Businesses that have loyal employees provide services of higher quality, they need less resources and efforts attracting investment, recruiting, selecting and training new employees. They are more productive and profitable. Consequently, employee loyalty is valued as the most important asset that helps the company to gain competitive advantage and differentiation. Seeking to benefit from employee loyalty it is important to know what factors build and affect employee loyalty so the authors’ of the paper aim was to compile a set of factors that affect employee loyalty.The authors analyzed Lithuanian and foreign scientific literature on employee loyalty and formulated the following definition of employee loyalty: it is building and supporting long-term and mutually beneficial and trust-based relationships between the business and its employees who are committed to and well disposed towards it. Employee loyalty is a set of factors that exist at individual and organizational level. At individual level, employee loyalty depends on an employee’s gender, age, education, length of working time, family status. At organizational level, it depends on employee development, empowerment, team work, management, salary, working conditions, leadership commitment to quality culture, employee performance assessment, thus, general employee satisfaction contributes to loyalty. These factors, if put into practice properly, can be beneficial for the business: boost sales and profit, reduce employee turnover, enhance quality, expand innovations, strengthen its public standing, improve employee reliability.
Keywords: employee loyalty; employee development; empowerment; management; satisfaction; commitment